以翻轉式概念構圖提升學生閱讀理解能力之研究 The Flip Concept Map in Relation to Student's Reading Comprehension Skills - 吳佳娣 Chia-Ti Wu; 范含芸 Han-Yung Fan; 陳秀燕 Siou-Yan Chen; 劉遠楨 Yuan-Chen Liu (Higher Education Foundation, 2016)
本研究以翻轉式概念構圖為教學策略，期望能提升學生的閱讀理解能力。研究對象為新北市某國小五年級學生，以立意取樣選取兩個班級作為實驗組及控制組，實驗組教師運用翻轉式概念構圖進行教學，控制組教師以傳統講述式進行大意教學。本研究採準實驗研究設計，歷時10週，共10堂課（400分鐘），研究結果發現，實驗組經由翻轉式概念構圖的教學，在「提取訊息」與「推論訊息」沒有顯著差異，但在「詮釋整合」與「比較評估」的能力明顯優於控制組，且實驗組之中的高學習成效學生經過實驗後，在「推論訊息」能力上與低學習成效學生沒有顯著差異，但在「提取訊息」、「詮釋整合」及「比較評估」的能力優於低學習成效的學生。因此，翻轉式概念構圖教學策略能有效提升學生的閱讀理解能力。 In this study, using fl ip concept mapping teaching strategy, hoping to enhance the students' reading comprehension. The participants is fi fth-grade students in a mountainous area of New Taipei City. Select two classes as the experimental group and a control group, experimental group for teachers to use fl ip concept mapping teaching, control group for teachers to use traditional teaching. Quasi-experimental design, which lasted ten weeks a total of ten lessons. The conclusions as following below: 1. Through fl ip concept map teaching, the "extract information" and "inference messages" of reading comprehension in experimental group shows nosignificant difference, but better than control group in ability of "explain integration" and "comparative assessment". 2. Through experiments, the higher learning effectiveness of experimental group students show no significant difference in "inference messages" with lower learning effectiveness students, but better than lower learning effectiveness students in ability of "extract information," "explain integration" and "comparative assessment".